Essential Oils of Three Conifer Species from FRIM’s Main Campus - J, Mailina; MA, Nor Azah; S, Saidatul Husni; ZP, Mohammad Faridz (EDUCATUM Journal of Science, Mathematics and Technology, 2018)
A study was performed to investigate the volatile constituents of three conifer species (Podocarpus neriifolius, Nageia motleyi and Dacrydium elatum) which were planted in the main campus of Forest Research Institute Malaysia (FRIM). The fresh leaves were extracted by Clavenger hydrodistillation apparatus and the essential oils were analysed by GC and GC/MS analysis. Analyses revealed that the P. neriifolius and N. motleyi oils were rich with sesquiterpenes and have monoterpenes in very trace amount. The major sesquiterpenes of P. neriifolius oil were phyllocladene (26.37%), kaurene (13.75%), bicyclogermacrene (12.14%) and followed by sandaracopimara-8(14), 15-diene (7.89%) and β-caryophyllene (6.25%). Meanwhile, the major components of N. motleyi oil were bicyclogermacrene (45.85%), viridiflorene (12.36%), globulol (9.48%) and germacrene D (6.15%). D. elatum oil has mono- and sesquiterpenes as its main components in which β-caryophyllene (29.03%), α-pinene (28.41%), phyllocladene (22.89%), α-humulene (4.27%) and pimaradiene (2.61%) were detected in this oil. The chemical compounds identified are responsible for the aroma of these selected conifer species and showed the potential of conifer plants as a source of aroma chemicals.